Magnetism of Manganese Complexes with Fluorinated Benzimidazole-Substituted Nitronyl Nitroxides - Tretyakov, Evgeny; Bakuleva, Nadejda; Efimov, Nikolay; Kulikova, Elizaveta; Luneau, Dominique (Inorganics, 2024)
A series of layered compounds of the formula {[Mn2(radical)3](ClO4)}n was obtained by a reaction (in methanol) of manganese(II) acetate with 2-(2-benzimidazolyl)-4,4,5,5-tetramethylimidazolidinyl-1-oxy-3-oxides fluorinated on the benzene ring and by successive addition of sodium perchlorate. This study showed that the magnetic properties of the complexes are sensitive to the number and arrangement of fluorine atoms in the paramagnetic ligands. It was found that the heterospin complex with 4-FBzIm-NN behaves as a magnet with Curie temperature TC = 50 K, which is close to that of the {[Mn2(BzIm-NN)3](ClO4)}n complex containing a nonfluorinated ligand. Meanwhile, no 3D ordering was noted for complexes with difluorinated and 5-fluoro-substituted ligands.